Political Thought And Its Impact On Codifying The Systems Of International Relations (Journal of the College of Basic Education, 2024)
The Islamic vision sets out to manage its international relations with countries that do not worship anyone other than God within the realistic recognition of their unity and codifies treaties and covenants with them to ensure the security of peace in the international community. Therefore, political thought adopts a set of theories, hypotheses and theses that are responsible and in control of the management of the internal and external systems of countries and are in control of their administration. Its international relations and these possibilities cannot be universal and cannot be applied in all countries unless they are based on the Islamic vision in managing international relations, no matter how realistic and moral it may be, because the basic and ultimate goal of it is colonialism, arrogance, ownership and control over the capabilities of peoples and societies.Reasons for choosing the topic: To demonstrate clear visions about the possibility and ability of the thought of the Islamic political system to manage the internal and external systems of societies, by re-interrogating the Islamic vision in a way that is commensurate with the ability of the first Islamic state upon its establishment to lead the societies under its shadow, rule and judge among them, and manage their affairs.Research problem: The research identifies the confusion regarding the separation between religion and the state, and rejects the visions that attempt to indicate the separation of religion from the state, with religion being content with being confined to the silo of worship, publishing fatwas, and not keeping pace with developments taking place in political systems, especially state administration systems.The importance of the research: Explaining the hypotheses and theories that determine the ability of the Islamic state to manage international relations, as Islamic political thought is based on keeping pace with developments in the systems of international relations and keeping pace with them to reach the implementation of the comprehensive Islamic system that idealizes and renews the systems to manage the internal and external policies of the state.Research hypotheses: The research imposes a mechanism for not applying the Islamic vision in the context of international relations, while relying on the strategy of global systems that is based on exploitation, arrogance, greed, and possession, thus controlling the capabilities of peoples and weakening them.The most important conclusions: The Islamic system has the ability to renew realistic systems by relying on the foundations of Islamic legislation and its sources - which are responsible for managing internal and external societies in a way that guarantees the safety of their members, denies injustice, tyranny, and vulnerability, and controls the capabilities of peoples, by establishing the principle of justice and equality in managing relations within Realistic recognition of the unity of states.The most important recommendations: Do not abandon the Holy Qur’an, and make it for blessing or to explain the legal rulings only, which do not exceed (5%) of its content, but rather try to interrogate its intellectual concepts and foundational laws because it contains integrated intellectual systems in establishing systems and codifying laws in various fields, especially the moderator of our research. International relations management